In the spirit of the Homo Videns era: Digital humanities databases and their potential for education - Lachowicz , Magdalena (Studia Historiae Oeconomicae, 2025)
The Author discusses the impact of the "homo videns" era on education, emphasizing the importance of visual literacy in a society increasingly dominated by images. She argues that the ability to analyze and interpret visual narratives critically is essential for students at all educational levels. Integrating visual thinking methods and documentary photography into the curriculum is necessary to enhance the effectiveness of teaching humanities and to adapt to the changing communication landscape shaped by media. The article highlights the historical significance of documentary photography in social reform, referencing influential figures like Lewis Hine and Jacob Riis, who used their work to advocate for labor rights and social change. The Author also explores the philosophical and semiotic dimensions of photography, suggesting that it serves as a cultural text that conveys historical context and societal values. The potential of photography as an educational tool is further reinforced by the availability of digital archives and social archives, which can enrich the learning experience and foster critical analytical skills among students. Finally, the author addresses the legal aspects of using visual materials in education, particularly concerning copyright laws and the importance of understanding Creative Commons licenses. She emphasizes the role of social archives in preserving local history and promoting civic engagement, while also pointing to various digital resources available to educators. By leveraging these tools and methodologies, educators can create innovative learning experiences that engage students in the exploration of history and culture through visual media. The text discusses a teaching method where a teacher provides a camera to students, encouraging them to photograph their social realities. This approach, sometimes used interchangeably with photo elicitation, allows students to select images that reflect their experiences and document specific social phenomena. The resulting photographic documentation should be well-planned and relevant for social or historical research. Teachers can offer guidance similar to that of Roy Striker or Charles Suchar, focusing on a central research question. This method can be adapted for various age groups and skill levels, serving as a foundation for education on social processes and self-evaluation of teaching practices.